Fungal diversity in different types of cheese and the effect of natamycin on their survival during Feta cheese manufacture and storage (Journal of Advanced Veterinary and Animal Research, 2016)
Objective: This study was planned to assess the distribution of yeasts and moulds in different types of cheese, and to study the effect of natamycin on their survival during manufacture of Feta cheese and its storage.Materials and methods: A total of 150 samples of local manufactured cheese were collected randomly from markets of Qena city in Egypt which were subjected for mycological examination by traditional microbiological examinations. The effects of different concentrations of natamycin on survival of yeasts and moulds in Feta cheese at room temperature, refrigeration condition, and pH values were evaluated.Results: Highest yeasts and moulds contaminations were recorded in Kareish cheese with a mean value of 2.40x106±9.72x105 and 4.64x102±1.18x102, respectively. The isolated moulds were mostly Cladosporium, Penicillium and Aspergillus, while yeast genera were species of Candida and Debaryomyces hansenii. Yeasts and moulds could not be detected after 24 h, and after curd in Feta cheese samples containing natamycin (at 0.2% or 0.4%) when the cheese samples were stored either at room or refrigeration temperature. Gradual decrease of pH value was also recorded in the cheese.Conclusion: Natamycin has strong antifungal activity and can extend cheese shelf-life during storage period.http://doi.org/10.5455/javar.2016.c152